MOTIVASI DAN PENGHAMBAT UKM KERAJINAN DI KOTA MALANG DALAM MENGELOLA SAMPAH MENJADI PRODUK KREATIF - Melvina Priscilia (Parsimonia - Jurnal Ekonomi dan Bisnis, 2018)
The increasing number of household waste encourages many Small Medium Enterprises (SMEs) to recycle garbage into creative products. This research aims to analyze entrepeneurs motivation and obstacle in recycling waste into creative products. This research employs a qualitative study with case study approach, involving 3 participants. The result of this research shows that both intrinsic and extrinsic motivation plays important role in driving SME entrepreneurs to recycle waste into crafts. Intrinsic motivation include interest and art skills in making crafts, eagerness to inspire other people to recycle waste, and environmental awareness. Extrinsic motivation consists of the increasing demand of artistry products, inexpensive raw materials, enormous profit, family support, and encouragement from government. Meanwhile, obstacles that are usually faced by entrepreneurs include difficulties in fulfilling high demand, long processing time, emotional mood of craftmen, limited human resources, various waste (raw material) conditions, low demand in Malang city. These obstacles are usually overcomed by using new material as waste substitute to fulfill order in large quantities only, employing additional workers, outsourcing production process to other craftmen, attending exhibition events that are held by government, and online selling. The research results are useful for developing campaign on sustainability marketing are suggested